2022
DOI: 10.1007/s10461-022-03683-9
|View full text |Cite|
|
Sign up to set email alerts
|

Stigmatizing Policies Interact with Mental Health and Sexual Behaviours to Structurally Induce HIV Diagnoses Among European Men Who Have Sex with Men

Abstract: Structural stigma shapes men who have sex with men’s (MSM’s) mental health and sexual behaviours. The aim of this study was to examine how stigmatizing policies interact with downstream anxiety/depression and sexual behaviours to structurally pattern HIV disparities among European MSM. We conducted a secondary data analysis of the European Men-who-have-sex-with-men Internet Survey (EMIS) from 2017. We included a total of 98,600 participants living in 39 European countries. We used the Rainbow Index, a score gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In addition to the development of scales to examine stigma among PLWH, several studies have also examined the effect of social support on stigma and depression. Previous studies have reported stigma is positive associated with depression ( Murphy et al, 2006 ; Kota et al, 2022 ; Stojanovski et al, 2022 ). A systematic review also reported PLWH living with HRS was 1.6 times more likely to suffer depression.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the development of scales to examine stigma among PLWH, several studies have also examined the effect of social support on stigma and depression. Previous studies have reported stigma is positive associated with depression ( Murphy et al, 2006 ; Kota et al, 2022 ; Stojanovski et al, 2022 ). A systematic review also reported PLWH living with HRS was 1.6 times more likely to suffer depression.…”
Section: Discussionmentioning
confidence: 92%
“…It was confirmed that HIV has little relevance from a PLWH perspective, and for this reason, anonymity and discretion are preferred [ 45 ]. Gabbidon et al (2020) [ 46 ] escribe a decision-making and outing process with HIV self-disclosure. Studies confirmed relationship quality as a determinant of risk and resilience factors in the disclosure process of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Greater social acceptance makes it easier for PLWH to live openly with their disease [ 54 ]. Studies show that policies addressing stigma against LGBTQ+ people are significant structural determinants of the HIV risk in Europe [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we found that even attained a high level of SC, MSM with a high level of IH still had a higher risk of condomless sex than those with a low level of IH. For those with a high level of SC, structural stigma may still shape the fear of being stigmatized and crisis sense of support loss from social contacts (e.g., family members, colleagues) [56,57]. External prejudice events (i.e., distal stressors) and IH might further increase the risk of condomless sex.…”
Section: Discussionmentioning
confidence: 99%